Do Movement Patterns and Habitat Use Differ Between Optimal- and Suboptimal-sized Northern Bobwhite Coveys? - Christopher K. Williams; Roger Applegate; Anthony R. Ives (National Quail Symposium Proceedings, 2017)
The group size of social animals and spatial structure of the environment can affect group behavior and movement decisions. Our objective was to investigate movement patterns and habitat use of northern bobwhite coveys (Colinus virginianus) of different size. Using radiotelemetry, we continuously monitored covey group size, daily movement, and habitat use on 12 independent 259-ha study areas in eastern Kansas, USA, during the winters between 1997 and 2000. We used correlated random walk models and fractal dimension models to determine if covey size affected movement characteristics or habitat selection. Intermediate-sized coveys (9–12 individuals, close to optimal covey size) exhibited daily movements that were substantially smaller and weekly home ranges that were more composed of woody escape cover than coveys of smaller or larger sizes. From the fractal dimension analyses, these coveys exhibited movement in between linear and a random walk at small spatial scales but very linear at large spatial scales. Large coveys had increased daily movement and tended to move in straighter lines (as indicated by the high proportion of turning angles [i.e., the angle between an initial direction and a new direction] around 0° and 180° and their multiscale fractal dimension) and they incorporated more cropland into their range, presumably to meet the feeding requirements of a larger group. In contrast, small coveys (1–4 individuals) tended to move more and increase the size of their home range, travel with a greater diversity of turning angles, and show movement patterns that were largely tortuous across a greater number of habitat patches at larger spatial scales (700 m). Small coveys have lower fitness and add new membership to increase fitness so it is possible that the movement behavior we observed represented a shift into a foray mode where bobwhites were searching for new membership. For areas with small populations and covey sizes, this information will help biologists better plan for habitat management to assist these coveys with their winter fitness.
Keywords: Colinus virginianus; northern bobwhite; correlated random walk; fractal dimension; habitat fragmentation; optimal group size